PERANAN APARATUR PEMERINTAH KECAMATAN DALAM MENSOSIALISASIKAN PAJAK BUMI DAN BANGUNAN (PBB) DI KECAMATAN BETUNG KABUPATEN BANYUASIN - Antartila Rezki Aziz (STIA SATYA NEGARA PALEMBANG, 2022)
ABSTRACTOne source of funding for government funding is in the form of Land and Building Tax (PBB). The Land and Building Tax can be utilized for various functions of determining policies related to land and buildings. The United Nations revenue contributes to relatively small tax revenues, but the Land and Building Tax is a very potential source of revenue for the region.This research was conducted at the Betung Sub-District Office. Researchers collected data by observation, documentation, and interviews with selected informants related to the socialization of Land and Building Tax (PBB) in Betung District, Banyuasin Regency.The results of this study indicate that (1) The Role of Betung District Government Apparatus in disseminating Land and Building Tax (PBB) in Betung District Banyuasin District shows the results that the efforts made by the Betung District apparatus as a form of responsibility, as officers who assist in achieving the objectives that have been planned by the Regional Government of Banyuasin Regency has not been maximized. (2) There are inhibiting factors in the socialization efforts such as the number of experts in the field survey and the lack of field transportation facilities that are inadequate to reach areas in Betung Subdistrict, so that the realization of the objectives cannot run optimally. . Keywords: Socialization, Land and Building Tax (PBB), and apparatus.